Subcellular targeting analysis of SDR-type hydroxysteroid dehydrogenases. - Filling, C; Wu, X; Shafqat, N; Hult, M; Mårtensson, E; Shafqat, J; Oppermann, U (2001)
Most mammalian hydroxysteroid dehydrogenases known thus far belong to the protein superfamilies of short-chain dehydrogenases/reductases (SDR) and aldo-keto reductases (AKR). Whereas members of the AKR family are soluble, cytoplasmic enzymes, SDR-type hydroxysteroid dehydrogenases are also located to other subcellular compartments, i.e. endoplasmic reticulum, mitochondria or peroxisomes. Differential localization might play an important role in influencing the reaction direction of hydroxy dehydrogenase/oxo reductase pathways by determining the available nucleotide cofactor pool. Targeting signals for different subcellular organelles in human hydroxysteroid dehydrogenases have been identified, however, in several enzymes localization signals remain to be determined.